Listening to the voices of undergraduate students: exploring astin’s theory of student involvement during the COVID-19 pandemic - Bee, Wah Tan; Nursafwah Tugiman,; Saidatul Nurul Hidayah Jannatun Naim NorAhmad,; Yen, Sin Foo (Penerbit Universiti Kebangsaan Malaysia, 2024)
The COVID-19 pandemic has profoundly impacted higher education, particularly in terms of student engagement in academic and extracurricular activities. This study aims to investigate the specific challenges faced by undergraduate students in maintaining their academic and extracurricular involvement during the pandemic. Employing Astin’s theory of student involvement as a theoretical framework, qualitative in-depth interviews were conducted with eight highly active undergraduate students. The findings reveal significant challenges both inside and outside the classroom. Outside the classroom, students struggled with ineffective teamwork, poor communication, and a lack of engagement in repetitive programmes. Inside the classroom, the shift to online learning led to participation shifts, increased workload, and stress due to non-conducive home environments and poor internet connections. The pandemic's impacts on students were mixed, with negative effects including increased stress and feelings of missed opportunities, while positive effects included enhanced resilience, patience, and problem-solving skills. Students suggested several strategies for improvement, such as administrative support for extracurricular activities, enhanced communication, and innovative teaching methods balancing synchronous and asynchronous learning. The study concludes with recommendations for fostering positive student-lecturer relationships and improving the overall educational experience. The findings underscore the need for universities to develop resilient and adaptable systems to support student engagement during future crises.